Addressing social determinants of health in pediatric health systems: balancing mission and financial sustainability. Issue 1 (9th February 2022) - Melzer, Sanford M.
Abstract : Purpose of review: With increasing recognition of the impact of poverty, racism and other social factors on child health, many pediatric health systems are undertaking interventions to address Social Determinants of Health (SDoH). This review summarizes these initiatives and recent developments in state and federal health policy impacting funding for these efforts. Recent findings: Although the evidence defining optimal approaches to identifying and mitigating SDoH in children is still evolving, pediatric health systems are making significant investments in different initiatives to address SDoH. With limited reimbursement available through traditional payment streams, pediatric health systems and Accountable Care Organizations are looking to value-based payments to help fund these interventions. Federal and state policy changes, including use of Medicaid funds for nonmedical interventions and introduction of the Accountable Health Communities model to pediatrics, offer additional funding sources to address SDoH. Summary: Initiatives among mission-driven pediatric health systems to address SDoH are increasingly common despite funding challenges. Value-based payments, expansion of Medicaid funding resulting from policy changes and delivery system reform, along with health system philanthropy and operating revenues, will all be needed to meet mission-based goals of addressing SDoH while supporting financial sustainability.